THE ROLE OF EDUCATION MANAGEMENT IN MANAGING THE SCHOLARSHIP PROGRAMME AND ITS IMPACT ON STUDENT ACHIEVEMENT - Erwin Erwin; Moh. Jenli Abbas; Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2024)
This research explores the role of education management in the management of scholarship programmes and their impact on student achievement. Effective education management plays an important role in ensuring that scholarship programmes are transparent, fair and efficient. A proper selection process, efficient fund management, as well as additional support such as academic guidance and mentoring, are crucial elements that education management must ensure. The results showed that students receiving scholarships had higher motivation and less financial pressure, which had a positive impact on their focus and academic performance. In addition, the additional support from the scholarship programme helps students face academic challenges and develop the required skills. Thus, the role of good education management in the management of scholarship programmes not only supports individual student achievement, but also contributes to improving the overall quality of education